The Interspecies Encounter Zones. Relations between dogs and humans [with “devil’s saliva in hearts” - Szperlik, Ewa (Poznańskie Studia Slawistyczne, 2021)
The subject of the literary study proposed in the title is the triptych by Josip Mlakić, which follows the convention of a futuristic anti-utopia. The work provides research material amenable to the application of diverse, interdisciplinary methodological tools (from ecocriticism to animal studies). In addition to the symbolic framing of the issue of dogs in cultural history, the starting point for the reflections on the post-apocalyptic vision of the totalitarian world (through which further wars swept and disturbed the ecosystem) is the post-humanist and post-anthropocentric perspective of the present and future human condition, with a particular focus on species chauvinism. In the Bosnian-Herzegovinian writer’s anti-war prose, speciesism (seen from the perspective of the complex relationship between dogs and humans) is also manifested in the blurring of the boundary between the concepts of animalism and humanity, in a vision of the world in which homo crudelis proves to be the greatest threat. In the world depicted by Mlakić, the relations between the man and the dog can be defined as an example of companion species, “nanoculture” realised in diverse “contact areas”. There also arises the question of hierarchical relations between people, entities with weak subjectivity: the excluded, the marginalised and all exterminated Others, including the disabled, who become subordinated “dogs” with the status of victims. The anticipated result of the study will be to present the function of literature as a source of reflection and a medium of expression (an invention, attributed to the humans) in relation to the concept of the twilight of anthropocentrism.